Resíduos de agrotóxicos em ameixa, maçã, pera e pêssego: desenvolvimento de métodos de análise e monitoramento - Kemmerich, Magali (2017)
In recent years, the indiscriminate use of pesticides and a lack of adoption of good agricultural practices have been evidenced by the results of analyzes of residues of pesticides in food. Thus, the goal of this work was to develop and validate two methods for determination of pesticide residues in plum, apple, pear and peach, with analysis by ultra high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). In the development of the QuEChERS method, different conditions of the extract clean-up were tested. In the validation results, the linear range of the method was 5 to 200 μg kg-1 with recoveries were between 70 and 120% and RSD ≤20%. The practical limit of quantification (LOQ) for 161 compounds was 10 μg kg-1. In MSPD optimization, different sorbents (C18, florisil®, PSA, alumina, amino, silica, chitosan, Oasis® HLB, StrataTM-X and fluoridated) were tested as solid support in different proportions with the sample. The homogenization was carried out with metallic spheres and extraction with acetonitrile and ultrasound. Accuracy and precision results obtained by MSPD were adequate for 131 pesticides residues studied, with recovery results ranging between 70 and 120%, with RSD ≤ 20%. The studied compounds presented practical LOQ of 10 μg kg-1. In the analysis of 100 samples of the studied fruits, different pesticides residues were found in concentrations ranging from <LOQ to 2.334,6 μg kg-1.